1990
DOI: 10.1084/jem.171.3.889
|View full text |Cite
|
Sign up to set email alerts
|

Association between protective efficacy of anti-lipopolysaccharide (LPS) antibodies and suppression of LPS-induced tumor necrosis factor alpha and interleukin 6. Comparison of O side chain-specific antibodies with core LPS antibodies.

Abstract: The core region of LPS has a relatively similar structure in various Gram-negative bacteria, whereas the outermost O side chains are responsible for the marked antigenic diversity among Gram-negative bacteria. O side chain-specific antibodies protect against homologous strains but not against heterologous strains in animal models . The core region of LPS is exposed at the surface of the O side chain-lacking rough mutants, among which Escherichia coli J5 and Salmonella minnesota R595 have been the most studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

1991
1991
1994
1994

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(56 citation statements)
references
References 23 publications
3
53
0
Order By: Relevance
“…Under the conditions used in this study, TNFa release by lymphocytes present in the PBMC fraction was negligible [19]. The cytotoxic activity of TNFa was measured on WEHI clone 13 cells as described [20,21].…”
Section: Methodsmentioning
confidence: 99%
“…Under the conditions used in this study, TNFa release by lymphocytes present in the PBMC fraction was negligible [19]. The cytotoxic activity of TNFa was measured on WEHI clone 13 cells as described [20,21].…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, using purified MoAb instead of crude hybridomal fluid, we could not demonstrate that HA-IA could be protective [26] in models very similar to those used by Teng et al [30]. In addition, in contrast to type-specific LPS antibodies, HA-IA did not suppress LPS-induced secretion of tumor necrosis factor in mice, a circumstance suggesting that HA-IA was not able to prevent LPS from reaching its target on macrophages [26].…”
Section: Studies With Monoclonal Antibodiesmentioning
confidence: 67%
“…Some investigators, however, were unable to obtain similar results [19][20][21][22][23][24][25][26][27][28]. For instance, Greisman and Johnston [27] found that mice inoculated with LPS from S. minnesota, Salmonella typhimurium, E. coli 0127, or E. coli 0111 were not protected by either of the two antisera to the J5 and Re mutants; the mortality among these mice was even greater than the mortality for mice that received only saline.…”
mentioning
confidence: 89%
See 2 more Smart Citations